2010
DOI: 10.1002/ajmg.a.33235
|View full text |Cite
|
Sign up to set email alerts
|

Speech–language characteristics of children with neurofibromatosis type 1

Abstract: Delays in speech and articulation development have been found in school-aged children and adolescents with neurofibromatosis type 1 (NF1). This report examines speech and language skills of preschool children with NF1. Nineteen 3- to 5-year-old children diagnosed with NF1 were assessed using measures of articulation (GFTA-2), and receptive and expressive language (CELF-P2). Significant differences were observed between mean scores obtained by the group of children with NF1 compared to the validated controls fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 34 publications
4
15
1
Order By: Relevance
“…We also observed a significant positive relationship between language abilities (receptive and expressive) and phonological awareness and memory, supporting previous findings in children without NF1 that oral language supports the development of preliteracy abilities . Previous research has reported a high incidence of language delays in young children with NF1, which raises the possibility that the high level of phonological processing deficits evident in our sample may have been related to the poorer language abilities reported in children with NF1.…”
Section: Discussionsupporting
confidence: 91%
“…We also observed a significant positive relationship between language abilities (receptive and expressive) and phonological awareness and memory, supporting previous findings in children without NF1 that oral language supports the development of preliteracy abilities . Previous research has reported a high incidence of language delays in young children with NF1, which raises the possibility that the high level of phonological processing deficits evident in our sample may have been related to the poorer language abilities reported in children with NF1.…”
Section: Discussionsupporting
confidence: 91%
“…The NF1 population has an increased incidence of speech and language issues (particularly oromotor deficits, including speech dyspraxia, which can improve with appropriate speech therapy), velopharyngeal insufficiency, misarticulation, and disfluency. 47,48 Problems with hearing are not typical for patients with NF1, and any suspicion about hearing problems should be approached as they would be for any other pediatric patient.…”
Section: Neurodevelopmentalmentioning
confidence: 99%
“…However, the presence of discrete thalamic T2 hyperintensities has been associated with severe and generalized cognitive dysfunction [9]. Speech and language disorders have been estimated to affect 18% to 58% of school-aged children and adolescents with NF1 [7,10] and 68% of preschoolers [11]. Children with NF1 often have mild generalized hypotonia in association with less well-developed gross motor skills than their unaffected peers, causing minimal functional impairment.…”
Section: Complicationsmentioning
confidence: 99%